Analisis Perbandingan Rasio Keuangan Dan EVA Sebagai Pengukur Kinerja Keuangan PT Kalbe Farma Tbk. - Fathimah, Siti Nurul; Awa, Anastasia; Afni, Nur; Holiawati, Holiawati (Universitas Pamulang, 2023)
The imbalance between the value of exports and the value of imports after COVID-19 creates problems for the financial performance faced by the pharmaceutical industry in Indonesia. The purpose of this analysis is to compare the company's performance using financial ratios and EVA, to determine the effectiveness of the company in managing its finances and assessing the performance of the company's management. This research is a comparative research with a quantitative approach. The data used is secondary data in the form of financial statements of PT Kalbe Farma Tbk for 2018-2022. Data analysis starts from the calculation of current ratio, ROE, DER, EVA, and financial performance. The research results obtained show positive results during the 2018-2022 period. This shows that the company's management has successfully managed its operational financing.